Long oligodeoxynucleotides: chemical synthesis, isolation via catching-by-polymerization, verification via sequencing, and gene expression demonstration - Yipeng Yin; Reed Arneson; Alexander Apostle; Adikari M. D. N. Eriyagama; Komal Chillar; Emma Burke; Martina Jahfetson; Yinan Yuan; Shiyue Fang (Beilstein Journal of Organic Chemistry, 2023)
Long oligodeoxynucleotides (ODNs) are segments of DNAs having over one hundred nucleotides (nt). They are typically assembled using enzymatic methods such as PCR and ligation from shorter 20 to 60 nt ODNs produced by automated de novo chemical synthesis. While these methods have made many projects in areas such as synthetic biology and protein engineering possible, they have various drawbacks. For example, they cannot produce genes and genomes with long repeats and have difficulty to produce sequences containing stable secondary structures. Here, we report a direct de novo chemical synthesis of 400 nt ODNs, and their isolation from the complex reaction mixture using the catching-by-polymerization (CBP) method. To determine the authenticity of the ODNs, 399 and 401 nt ODNs were synthesized and purified with CBP. The two were joined together using Gibson assembly to give the 800 nt green fluorescent protein (GFP) gene construct. The sequence of the construct was verified via Sanger sequencing. To demonstrate the potential use of the long ODN synthesis method, the GFP gene was expressed in E. coli. The long ODN synthesis and isolation method presented here provides a pathway to the production of genes and genomes containing long repeats or stable secondary structures that cannot be produced or are highly challenging to produce using existing technologies.